XML Markup for maintenance management of critical care medical devices - Escobar, P. (2015)
Preventive maintenance of biomedical devices is of particular concern to avoid failures and breakdowns, especially for critical care and life supporting devices. Signs of potential failures are not always visible and so, they should be inspected and tested periodically using the appropriate technology. Patient simulators have become one of the essential tools for any biomedical department on every health institution, but its cost is still high to be afforded by everyone. The Labview interactive virtual instrument SIMPAC, a simple PC-based patient simulator, showed to be a low cost powerful tool for simulation of healthy and pathological conditions using signals repositories of different biomedical devices such as EEG, ECG, etc., and also to record the output signals of devices like pacemakers, defibrillators, etc. Here we present an enhancement of the tool which consists of adding a secure reporting feature using XML for presenting tests results, applying digital signature for granting report integrity, assuring this way that reports can not be altered by intentional or accidental manipulation of the data contained on it, according to the terms of the medical technology law. In addition, SIMPAC brings a low cost solution for teaching and practical purposes.